Aqua(hippurato)bis(1,10-phenanthroline)cobalt(II) nitrate monohydrate - Gui-Quan Guo; Ji-Hua Deng; Jing Chen (Acta Crystallographica Section E, 2010)
In the title compound, [Co(C9H8NO3)(C12H8N2)2(H2O)]NO3·H2O, the CoII atom is six-coordinated by a carboxylate O atom of the hippurate (Hc) anion, a water O atom and four N atoms from two 1,10-phenanthroline ligands in a distorted octahedral geometry. The uncoordinated O atom of the hippuric acid anion is involved in an intramolecular hydrogen bond to the coordinated water molecule. The crystal packing is stabilized by intermolecular O—H...O hydrogen bonds involving the Hc anions, the coordinated water molecule, the nitrate anion and the uncoordinated water molecule.